2003
DOI: 10.1177/146642400312300114
|View full text |Cite
|
Sign up to set email alerts
|

The survival and recovery of bacteria in vacuum cleaner dust

Abstract: The possibility exists that environmental dust could be a source of gastro-intestinal infection in the domestic environment and that the causative microbes are collected during vacuum cleaning. This study examines the survival of total bacterial populations, Enterobacteriaceae and salmonella species in vacuum cleaner dust in vitro and in use. Total counts remain constant at around 10(6)-10(8) colony forming units (cfu) g-1 for at least 60 days. Enterobacteriaceae showed only a slight decline over the same peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
(18 reference statements)
1
19
0
Order By: Relevance
“…Vacuums can represent a reservoir for antibiotic resistance genes, and those genes may remain stable and were detectable using a molecular approach in this study, in keeping with previous results for bacteria (8). The possible impact of this reservoir on spreading of drug resistance to humans is unclear.…”
Section: Less (4e6 16s/g Of Dust)supporting
confidence: 75%
See 1 more Smart Citation
“…Vacuums can represent a reservoir for antibiotic resistance genes, and those genes may remain stable and were detectable using a molecular approach in this study, in keeping with previous results for bacteria (8). The possible impact of this reservoir on spreading of drug resistance to humans is unclear.…”
Section: Less (4e6 16s/g Of Dust)supporting
confidence: 75%
“…(5,6) and other bacteria, including Clostridium botulinum (7). Environmental dust could be a source of gastrointestinal infection in the home environment, and the causative microbes collected during vacuum cleaning can remain viable in vacuum dust bags or chambers over extended periods (8).…”
mentioning
confidence: 99%
“…The only concern raised regarding samples received from the operators was that some boot swabs had dried out by the time they had arrived. Salmonella is able to survive in dry conditions better than other Enterobacteriacae (Haysom and Sharp, 2003), and Salmonella has been recovered from dried litter and faeces up to 26 months old (Davies and Wray, 1996;Davies and Breslin, 2003). Therefore, the drying out of boot swabs may not be of major concern for the detection of high numbers of organisms, but low levels may not survive during transit.…”
Section: Condition Of the Samplesmentioning
confidence: 99%
“…It has also been reported that aerosolization of carpet dust can be a source to spread other pathogenic bacteria such as Salmonella and Clostridium botulinum [28]. What make things worse is that the presence of such microorganisms in dust bags or the chambers of the vacuum cleaners can be extended over long periods of time [29]. The amount of dust present in the A/C and carpets varied considerably.…”
Section: IVmentioning
confidence: 99%